Financial planning for educational institutions SMP Cahaya Rancamaya Islamic Boarding School - Nazarullah Mawardi Arsyad; Endin Mujahidin; Nesia Andriana; Mowafg Abrahem Masuwdd (At Turots: Jurnal Pendidikan Islam, 2025)
Financial planning is an essential component in ensuring the sustainability and operational quality of educational institutions. This study aims to analyze the financial planning at SMP Cahaya Rancamaya, focusing on the implementation of priority-based planning, which includes operational budgeting, facility development, and quality improvement programs. The research employs a qualitative method with a descriptive analysis approach to provide an in-depth depiction of financial planning implementation. The findings reveal that the challenges faced are not particularly significant, as evidenced by the institution's well-functioning operations and the successful construction of a new building with a capacity of 300–350 students, specifically designated for female students in the upcoming academic year. Financial planning is carried out based on financial management principles, including legal foundations, clear funding sources, and the execution of financial management functions. Furthermore, the institution has established structured guidelines for financial planning and management to support the achievement of the school's strategic goals. These findings emphasize the importance of well-prepared financial planning in supporting the sustainability and development of educational institutions.